Peran E-Wom dalam Memediasi Pengaruh Influencer, Brand trust, Brand Image, dan Social Media Marketing terhadap Keputusan Pembelian - Kurniasih, Indri; Sukarno, Aji; Yulia Rosyada, Fani; Artanti, Anisrina; Wahyudi, Budi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The objective of this research is to analyze the influence of the variables influencer, brand trust, brand image, and social media marketing on the purchase decision of Glad2Glow skincare products, with electronic word of mouth (e-WOM) as the mediating variable. This study utilizes a quantitative approach with primary data. The sampling technique employed was purposive sampling, involving 160 female respondents aged at least 17 years, residing in the Jabodetabek area, and who have purchased Glad2Glow products. Data collection was performed through the distribution of questionnaires. Data analysis was conducted using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The analysis process included two main stages: (1) Outer model testing, covering convergent validity, discriminant validity, and reliability; (2) Inner model testing, covering the goodness of fit test, coefficient of determination (R^2) test, hypothesis testing, and predictive relevance (Q^2) test. The results of the analysis indicate that influencer, brand trust, and social media marketing have a significant influence on e-WOM. Brand trust and e-WOM are proven to have a significant influence on purchase decisions. Simultaneously, the four independent variables (influencer, brand trust, brand image, and social media marketing) have a significant influence on e-WOM and purchase decisions. The mediation effect analysis reveals that only brand trust has a significant indirect influence on purchase decisions through e-WOM. Among the variables studied, the influencer is the most dominant factor in influencing e-WOM, while brand trust is the most dominant variable in influencing purchase decisions.